Characterisation of Two Photosensitizing Compounds from Typhonium Flagelliforme Schott and Their Mode of Action in Inducing Cancer Cell Death - Ho, Anthony Siong Hock (2002)
A bio-assay guided approach was used to isolate photosensitizing compounds from Typhonium flagelliforme Schott, a plant considered by local communities to possess anticancer properties. Two putative photosensitizers, pbeophorbide-a and a possible novel derivative, 13-2, 17-dihydroxyethyl pheophorhide-a were isolated using column chromatography and purified on thin layer chromatography under low light conditions. The phototoxic effect of pheophorbide-a and 13-2, 17-dihydroxyethyl pheophorbide-a on the growth of a variety of human cell lines was tested using the MIT assay. Both photosensitizers were inactive in the dark but when activated by light, mediated cell killing with IC₅₀ values ranging from 0.12 to more than 4 µg/ml, with the leukemic cells being the most sensitive. Photodynamic cell killing was dependent on photosensitizer concentration, irradiation dose and drug incubation time. Preliminary characterization showed that both compounds tended to aggregate in aqueous solution and the aggregation was augmented by the presence of serum proteins. This correlated to a decrease in cytotoxic efficacy as the amount of serum in the media was increased suggesting that binding to serum proteins reduced drug uptake and possibly altered intracellular localization patterns. It bas been shown that photosensitizers mediate cell-killing through a free radical (Type I) or singlet oxygen (Type II) dependent reaction. Indirect tests showed that the major species generated by photoactivation using pheophorbide-a and 13-2, 17-dihydroxyethyl pheophorbidea was singlet oxygen molecules with a minor contribution by other radical species. Furthermore, confocal laser scanning microscopy showed that these fluorescent photosensitizers accumulated in lysosomes, suggesting that the release of hydrolytic enzymes may be a common mechanism leading to necrotic injury. However, whereas some cell lines also showed intense membrane and cytoplasmic staining, others showed some mitochondrial accumulation, suggesting that other mechanisms may also contribute to cell-killing. Commercially available PDT compounds, including hypericin, appear to kill cells by inducing apoptosis. The treatment of HL60 cells with pheophorbide-a and 13-2, 17-dihydroxyethyl pheophorbide-a resulted in the appearance of typical apoptotic morphology, including membrane blebbing, apoptotic bodies, cell shrinkage and DNA-Iaddering, suggesting that these compounds also induce apoptosis. Singlet oxygen is thought to be the primary stimulus driving the induction of apoptosis and this was studied by using the singlet oxygen quencher sodium azide. The caspase family of proteases, which are inhibited by the peptide Z-V AD-FMK, are regarded as the main effectors of apoptosis. Zinc ions are inhibitors of endonucleases that cause apoptotic DNA fragmentation. We found that both sodium azide and Z-V AD-FMK effectively reduced the incidence of apoptosis induced by pheophorbide-a and 13-2, 17-dihydroxyethyl pheophorbide-a. Zinc did not affect 13-2, 17-dihydroxyethyl pheophorbide-a induced apoptosis but reduced pheophorbide-a induced apoptosis. Cycloheximide, a protein synthesis inhibitor, did not decrease the incidence of apoptosis for either photosensitizer but actually increased 13-2, 17-dihydroxyethyl pheophorbide-a induced apoptosis. These results support the role of singlet oxygen as primary inducers and caspases as effectors of apoptosis. PDT induced apoptosis does not require the synthesis of new proteins but PDT may, in the case of 13-2, 17-dihydroxyethyl pheophorbide-a, induce the synthesis of proteins that protect cells from further oxidative damage. The results also suggest that PDT with 13-2, 17-dihydroxyethyl pheophorbide-a may activate an endonuclease that is not inhibited by zinc. The progression of apoptosis is highly regulated by pro-(Bax) and anti- apoptotic Bcl-2 family of proteins (Bcl-2, Bel-XL). Qualitative detection of these apoptotic marker proteins at time intervals of 4, 8, 12 and 24 hours showed that the ratios of Bax to Bcl-2 and of Bax to Bcl-XL were markedly increased from 12 hours onwards and this, as has been suggested earlier, is a marker for apoptotic progression. However, because apoptosis can be detected as early as 2 hours post irradiation, Bcl-2 proteins may not play a major role in the initial induction of apoptosis but impacts apoptosis at a much later stage, possibly to ensure the complete demise of the cell. In conclusion, pheophorbide-a and 13-2, 17-dihydroxyethyl pheophorbide-a are effective photosensitizing compounds that kill cells mainly through apoptosis. The possibility of different apoptotic pathways being induced, especially by 13-2, 17-dihydroxyethyl pheophorbide-a, makes the development of these compounds as potential clinical drugs, an exciting prospect.